Measurement properties of quality of life measurement instruments for infants, children and adolescents with eczema: protocol for a systematic review - Heinl, Daniel; Prinsen, Cecilia A. C.; Drucker, Aaron M.; Ofenloch, Robert; Humphreys, Rosemary; Sach, Tracey; Flohr, Carsten; Apfelbacher, Christian (Systematic Reviews, 2016)
Eczema is a common chronic or chronically relapsing, inflammatory skin disease that exerts a substantial negative impact on quality of life (QoL). The Harmonising Outcome Measures for Eczema (HOME) initiative has used a consensus-based process which identified QoL as one of the four core outcome domains to be assessed in all eczema clinical trials. A number of measurement instruments exist to measure QoL in infants, children, and adolescents with eczema, and there is a great variability in both content and quality of the instruments used. Therefore, the objective of the proposed research is to comprehensively and systematically assess the measurement properties of the existing measurement instruments that were developed and/or validated for the measurement of patient-reported QoL in infants, children, and adolescents with eczema.
Gesehen am 12.05.2020